PERBEDAAN HASIL BELAJAR MENGGUNAKAN MODEL PBL BERBANTUAN NEARPOD DENGAN MODEL PBL BERBANTUAN PPT - Lisana Oktavisanti Mardiyana; Diva Catur Kurniawan; Irmadatus Sholekhah (Jurnal Pendidikan Ekonomi (JURKAMI), 2026)
The study aims to determine the differences in learning outcomes  in implementing the Nearpod-assisted PBL model with PowerPoint. The research location at SMAN 1 Gambiran is a research sample of class X4 students as the control class and class X1 as the experimental class. The experimental method is a Posttest Nonequivalent Control Group Design. Treatment through the same learning model with different media. The following stages through the process of normality testing, homogeneity and hypothesis testing applying the T test. Related results show there are significant differences in learning outcomes for both classes. The average acquisition of the experimental class is 82.44, the value is higher than the control class of 74.25. Thus, it can be concluded that the PBL model assisted by Nearpod has a significant influence on learning outcomes. This study has several limitations including the research sample only involving two classes and only focusing on students' cognitive learning outcomes has not examined other aspects such as learning motivation or critical thinking skills. The study was conducted in a relatively short time so it has not shown the long-term impact of using the Nearpod-assisted PBL model on student learning outcomes.